A taxonomic revision of the augochlorine bee genus Ceratalictus Moure (Hymenoptera, Apoidea) - Coelho, Beatriz W. T.; Gonçalves, Rodrigo B. (Zootaxa, 2010)
The Neotropical halictid bee genus Ceratalictus Moure (Augochlorini) is revised. Five new species are described, Ceratalictus argentinus n. sp., C. camargoi n. sp., C. culminis n. sp., C. nitidus n. sp. and C. orthocarinatus n. sp.; five species are redescribed: Ceratalictus allostictus Moure, C. clonius (Brèthes), C. ischnotes (Vachal), C. psoraspis (Vachal), and C. stigon (Vachal). Ceratalictus lorenzinis (Strand) is synonymized with C. clonius. All catalogued type specimens were examined. Illustrations of all species and an identification key for the 10 presently recognized species are provided.